2016
DOI: 10.18632/oncotarget.10631
|View full text |Cite
|
Sign up to set email alerts
|

5-aza-2′-deoxycytidine (DAC) treatment downregulates the HPV E6 and E7 oncogene expression and blocks neoplastic growth of HPV-associated cancer cells

Abstract: High-risk human papillomaviruses (hr HPVs) may cause various human cancers and associated premalignant lesions. Transformation of the host cells is triggered by overexpression of the viral oncogenes E6 and E7 that deregulate the cell cycle and induce chromosomal instability. This process is accompanied by hypermethylation of distinct CpG sites resulting in silencing of tumor suppressor genes, inhibition of the viral E2 mediated control of E6 and E7 transcription as well as deregulated expression of host cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 64 publications
(74 reference statements)
3
25
0
2
Order By: Relevance
“…When cells transfected with siRNAs targeting p16 or/and MGMT as well as cells stimulated with 5‐Aza‐dC, the expression of p53, p21, and Rb was up‐regulated more significantly, and E6 and E7 expression down‐regulated significantly. Stich et al also found that treatment with 5‐aza‐2′‐deoxycytidine strongly decreases the expression of E6 and E7 in a panel of HPV‐transformed cervical cancer and head and neck squamous cell carcinoma cell lines . Zhang et al showed that upon demethylation treatment with 0.5‐μM 5‐aza‐dc for 96 hours, the expression of E6 and E7 mRNA was significantly decreased in UM‐SCC47 and CaSki cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cells transfected with siRNAs targeting p16 or/and MGMT as well as cells stimulated with 5‐Aza‐dC, the expression of p53, p21, and Rb was up‐regulated more significantly, and E6 and E7 expression down‐regulated significantly. Stich et al also found that treatment with 5‐aza‐2′‐deoxycytidine strongly decreases the expression of E6 and E7 in a panel of HPV‐transformed cervical cancer and head and neck squamous cell carcinoma cell lines . Zhang et al showed that upon demethylation treatment with 0.5‐μM 5‐aza‐dc for 96 hours, the expression of E6 and E7 mRNA was significantly decreased in UM‐SCC47 and CaSki cells .…”
Section: Discussionmentioning
confidence: 99%
“…Stich et al also found that treatment with 5-aza-2′deoxycytidine strongly decreases the expression of E6 and E7 in a panel of HPV-transformed cervical cancer and head and neck squamous cell carcinoma cell lines. 31 Zhang et al showed that upon demethylation treatment with 0.5-μM 5-aza-dc for 96 hours, the expression of E6 and E7 mRNA was significantly decreased in UM-SCC47 and CaSki cells. 32 33 Rb, p53, and p21 protein expression was increased in the p16-silenced cells compared to control siRNA-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other statistical analyses were done using Fisher exact and t test. Restoring p53 protein expression and tumor suppressor functions has been suggested as a promising strategy to combat HPV þ cancer, and the 5-aza structural analogue 5-aza-2 0 -deoxycytidine (decitabine) was recently found to increase p53 protein levels in HPV þ cervical and head and neck cancer cells (32). p53 is a powerful transcription factor able to transactivate proapoptotic and growth-inhibitory genes.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation status of genes can be reversed by a methyltransferase inhibitor, 5‐AZA‐dC, a deoxycytidine analog that has been approved by the U.S. Food and Drug Administration for the treatment of myelodysplastic syndromes. It has shown promising effects on treating certain solid cancers . 5‐AZA‐dC can reactivate silenced suppressor genes by promoter demethylation .…”
Section: Discussionmentioning
confidence: 99%